Perancangan Website Sebagai Sarana untuk Mempertemukan Supplier dengan Dropshiper - Taufik Hidayat; Yulindon Yulindon; Rahmat Hidayat (ULTIMA InfoSys, 2020)
Dropshipping or dropship is a form of trade where resellers or retailers make sales without stocking goods. A website is needed to facilitate suppliers in finding a dropshipper. Website creation needs programming languages, such as PHP and MySQL as the DBMS. However, a model is required to create a software. One of the software development models is Waterfall. It is a sequential software development model that ranges from analysis to maintenance stages.